Acceptance, empathy and congruence of parents in perception of teenage children - Juroszek, Weronika (Studia Psychologica: Theoria et praxis, 2010)
The study investigates whether sons differ from daughters in how they per ceive mothers and fathers. 267 participants (136 girls and 131 boys) completed Questionnaire of Parent Perception, built on basis of the Perception Question naire of therapist C. Rogers. Participants assessed the level of acceptance, empathy and congruence of their parents. The following results were obtained: mothers were perceived as morę accepting, empathic and congruent than fathers. The results showed that daughters assessed fathers as less congruent and empathic than sons did. Implications of these findings are discussed.